2017
DOI: 10.1093/jcr/ucx085
|View full text |Cite
|
Sign up to set email alerts
|

Political Ideology and Consumer Research beyond Complaining Behavior: A Response to the Commentaries

Abstract: Two commentaries on our article offer interesting and useful paths for pushing forward the research stream we have developed. Jost, Langer, and Singh suggest delving more deeply into underlying psychological motives while extending our finding to consumer boycotting behavior, and Crockett and Pendarvis suggest broadening the scope to consider the sociocultural context in which complaining occurs. We discuss these two complementary approaches. Building on these ideas, we offer five research themes we believe ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…We make several contributions, first by responding to calls for more research on mitigation in marketing (e.g., Mende and Scott 2021) and for considering consumer behavior through the lens of geopolitical, institutional, and marketplace systems (Jung et al 2017). Our research entails understanding, measuring, and assuaging potentially harmful consequences of institutional internal threats to national identity on brand sales.…”
Section: Research Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…We make several contributions, first by responding to calls for more research on mitigation in marketing (e.g., Mende and Scott 2021) and for considering consumer behavior through the lens of geopolitical, institutional, and marketplace systems (Jung et al 2017). Our research entails understanding, measuring, and assuaging potentially harmful consequences of institutional internal threats to national identity on brand sales.…”
Section: Research Contributionmentioning
confidence: 99%
“…We focus on institutional threats because the relationships between marketplace and institutions, despite their importance, are often neglected in the marketing literature (Jung et al 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the current research, political ideology is proposed as one explanatory factor as to why consumers' reactions to AI-delivered financial services are likely to differ. A consumer's political ideology has been shown to underpin how they will interact with society (Jung et al, 2017) with consumers who align to a political ideology, displaying similar opinions and behaviours (van AI financial service delivery . Previous research has identified that a consumer's political ideology underpins their emotional reactions (Northey et al, 2020), their attitudes (Kaikati et al, 2017) and their behaviours (Crockett and Wallendorf, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the current research, political ideology is proposed as one explanatory factor as to why consumers’ reactions to AI-delivered financial services are likely to differ. A consumer’s political ideology has been shown to underpin how they will interact with society (Jung et al. , 2017) with consumers who align to a political ideology, displaying similar opinions and behaviours (van Esch et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%